2002
DOI: 10.1210/jc.2002-020896
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Sensitivity and the Insulin-Like Growth Factor System in Prepubertal Boys with Premature Adrenarche

Abstract: Girls with premature adrenarche (PA), similar to women with polycystic ovarian syndrome, display alterations in the IGF system, may have impaired insulin sensitivity, and demonstrate unfavorable lipid profiles. Girls with PA are also at increased risk for functional ovarian hyperandrogenism. Metabolic studies in boys with PA, however, are limited. The objective of this study was to determine whether boys with PA show alterations in insulin sensitivity and the IGF system. We studied an ethnically heterogeneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 61 publications
(48 reference statements)
5
40
0
1
Order By: Relevance
“…SHBG is regulated by insulin and therefore hyperinsulinemia in obesity might be responsible for the decreased SHBG levels. [43][44][45] Obese girls had elevated mean testosterone levels between 10 and 14 years of age compared to reference values. The origin of testosterone production in girls might be adrenal and possibly also ovarian.…”
Section: Laboratory Markers Of Pubertal Developmentmentioning
confidence: 86%
“…SHBG is regulated by insulin and therefore hyperinsulinemia in obesity might be responsible for the decreased SHBG levels. [43][44][45] Obese girls had elevated mean testosterone levels between 10 and 14 years of age compared to reference values. The origin of testosterone production in girls might be adrenal and possibly also ovarian.…”
Section: Laboratory Markers Of Pubertal Developmentmentioning
confidence: 86%
“…Some studies have implicated that girls with premature adrenarche seem to be at increased risk of ovarian hyperandrogenism, polycystic ovarian syndrome (12), insulin resistance, and metabolic syndrome (13,14). Therefore, we found it important to study the timing of gonadarche and pubarche and the possible associations with adrenal androgen levels and fat accumulation in healthy Danish children.…”
Section: Introductionmentioning
confidence: 94%
“…Later on, Ibanez et al (76) published a number of casecontrol studies in lean Spanish (Catalonian) girls with a history of PP that showed evidence of insulin resistance based on both fasting insulin levels and the insulin response to a standard oral glucose tolerance test (OGTT) (76)(77)(78)(79)(80). Interestingly, these observations could not be confirmed in boys from the same population (81) but similar findings were obtained in pre-pubertal boys with PA from North America (82). In PP girls from North America, an inverse correlation between insulin sensitivity and ACTH-stimulated D5-androgen precursors (17-hydroxypregnenolone, DHEA) has been found; however, the study population was not body mass index (BMI) matched (83).…”
Section: Metabolic Risk Factors In Pamentioning
confidence: 99%